Character Costume as a Marker in Modern Ukrainian Cinema - Alfоrova Zoya (HUDPROM: The Ukrainian Art and Design Journal, 2025)
The article examines the marker-specific features of costume in contemporary Ukrainian cinema. Its purpose is to conceptualize the character’s costume as a semiotic marker within the modern Ukrainian film context. The Ukrainian films selected for analysis are not intended to constitute a fully representative corpus for the stated problem, which remains insufficiently explored in the domestic art-historical discourse. The analyzed examples of costume marker features in modern Ukrainian cinema reveal their principal manifestations, representing indicators of character traits in both male and female costume design. The research methodology draws on general theoretical approaches, formal-stylistic analysis, and coloristic examination of costumes for male and female characters in films produced during Ukraine’s independence period. The author engages with publications that investigate the state of academic discourse in Ukraine and abroad on the given issue. Through case studies of cinematic costumes designed by Antonina Belinska, Olena Gres, Maria Kvitka, Iryna Kliba, Nadiya Kudryavtseva, Olha Navrotskaya, Gala Otenko, Lyudmyla Semykina, Svitlana Symonovich, Tetyana Fedotova, and Natalia Tsybulko, the study demonstrates a direct correlation between a film’s creative concept and the costume design of its characters. In cinema, costumes function as a critical component in constructing character identity, shaping the visual narrative, and enhancing the film’s atmosphere, while consistently reflecting the contextual framework of cinematic action. The analysis identifies recurrent marker characteristics of costumes, including social-status and class indicators; psychological and individual traits; gender-specific features; markers of age and educational background; ideological and symbolic attributes; as well as narrative markers that allow for tracing the evolution of a character’s image throughout the film. It is concluded that all aspects of costume – from silhouette to ornamentation – participate in the process of character marking as an integral element of the film’s figurative structure.